Meningioma transcription factors link cell lineage with systemic metabolic cues. Issue 10 (12th April 2018) - Du, Ziming; Brewster, Ryan; Merrill, Parker H; Chmielecki, Juliann; Francis, Josh; Aizer, Ayal; Abedalthagafi, Malak; Sholl, Lynette M; Geffers, Lars; Alexander, Brian; Santagata, Sandro
Abstract: Background: Tumor cells recapitulate cell-lineage transcriptional programs that are characteristic of normal tissues from which they arise. It is unclear why such lineage programs are fatefully maintained in tumors and if they contribute to cell proliferation and viability. Methods: Here, we used the most common brain tumor, meningioma, which is strongly associated with female sex and high body mass index (BMI), as a model system to address these questions. We screened expression profiling data to identify the transcription factor (TF) genes which are highly enriched in meningioma, and characterized the expression pattern of those TFs and downstream genes in clinical meningioma samples as well as normal brain tissues. Meningioma patient-derived cell lines (PDCLs) were used for further validation and characterization. Results: We identified 8 TFs highly enriched in meningioma. Expression of these TFs, which included sine oculis homeobox 1 (SIX1), readily distinguished meningiomas from other primary brain tumors and was maintained in PDCLs and even in pulmonary meningothelial nodules. In meningioma PDCLs, SIX1 and its coactivator eyes absent 2 (EYA2) supported the expression of the leptin receptor (LEPR), the cell-surface receptor for leptin (LEP), the adipose-specific hormone that is high in women and in individuals with high BMI. Notably, these transcriptional regulatory factors, LEPR and LEP, both contributed to support meningioma PDCLs proliferation and survival, elucidating a survival dependency on both a core transcriptional program and a metabolic cell-surface receptor. Conclusions: These findings provide one rationale for why lineage TF expression is maintained in meningioma and for the epidemiological association of female sex and obesity with meningioma risk.